1996
DOI: 10.1007/bf00014132
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between vertical microdistribution and adaptations to oxygen stress in littoral Chironomidae (Diptera)

Abstract: Animals that dwell at different depths in the sediment, are adapted to different respiratory environments . It is possible that animals that occur deep in the sediment have a higher hemoglobin concentration than surfacedwelling animals . To test this hypothesis, hemoglobin concentrations and weights of eight chironomid species that dwell in the littoral zone were measured . High hemoglobin concentration and weight both seemed to contribute to an ability to cope with low oxygen concentrations, and determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…Polypedilum was the dominant genus in both environments. This can be explained by the fact that this group is cosmopolitan, opportunistic and relatively resistant to adverse conditions (Panis et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Polypedilum was the dominant genus in both environments. This can be explained by the fact that this group is cosmopolitan, opportunistic and relatively resistant to adverse conditions (Panis et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Tanytarsus (van der Wulp 1984) was the most abundant genus, with a broad distribution in all regions of the reservoir. Because this genus has low blood hemoglobin concentration (Panis et al 1996), it indicates environments with good water quality. Ligeiro et al (2013) indicated that the IDI is a good descriptor of disturbances at different spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…The larvae used in this study could belong to different species. For example, in lakes and fish-ponds C. plumosus (L.) is the most abundant (Matěna, 1995, Panis et al, 1996 while in polluted rivers C. riparius Meigen is abundant (Groenendijk et al, 1998). Larval survival decreased when the cyanotoxin concentrations were much higher than those recorded in the lake.…”
Section: Discussionmentioning
confidence: 99%